Study On The Effect Of Shifting 'Zero' In Output Membership Function On Fuzzy Logic Controller Of The Rov Using Micro-Box Interfacing - Mohd Aras, Mohd Shahrieel; Abdul Azis, Fadilah; Abdullah, Shahrum Shah; Lee, Dai Cong; Lim , Wee Teck; Ali, Fara Ashikin; Othman, Muhammad Nur (Penerbit UTM Press, 2015)
-